Migrant bodies and medical bordering: travelling for health reasons from Guinea-Bissau to Portugal. (3rd March 2020) - Formenti, Ambra
In a world where people's increasing mobility coexists with the multiplication of borders, migration for health reasons brings to light the contradiction between humanitarian principles and the tightening of migration policies. In this article, I address contemporary debates on border-making, biopolitics, humanitarianism and migration policies, by focusing on the case of Bissau-Guinean patients who arrive in Portugal under the terms of an international cooperation agreement on health. Drawing on patients' life stories and interviews with health professionals, I explore the ways in which medical bordering devices are exercised on migrants' bodies in hospitals, in order to test the truthfulness of their demands for care and, ultimately, the legitimacy of their stay in Portugal. Finally, I analyse the impact of these practices on the lives of patients and their strategies for dealing with them.